THE EVALUATION OF EMPATHY LEVEL OF UNDERGRADUATE DENTAL STUDENTS IN PAKISTAN: A CROSS-SECTIONAL STUDY - Javed, Muhammad Qasim (Journal of Ayub Medical College Abbottabad, 2019)
Background: Empathy is of significant importance in the dentist-patient relationship. The objective of the current study was to assess the empathy level of students at the culmination of their respective academic year, studying in first to fourth year across the undergraduate dental school of Pakistan. Methods: The cross-sectional study of undergraduate dental students was carried out at the dental school of Riphah International University in Islamabad, Pakistan in 2017. The survey was conducted with each class as they approached near the completion of their academic year. The Jefferson Scale of Physician Empathy- Health Professions Student Version (JSE-HPS version), was used in the study for measuring empathy. JSE-HPS is a valid and reliable self-reporting instrument comprising of 20 items. The total score on this instrument ranges between 20 and 140. ANOVA test and Independent sample t-test were used to analyze the data on SPSS 24. Results: Two hundred and twenty-two students participated in this study. The mean empathy score of students was 101.15±13.73. The mean empathy score of the first-year dental students was the highest (104.70±15.53) followed by the scores of second year students (102.70±13.48); the third-year class had the lowest mean empathy score (98.63±11.53) that corresponded to the first year of clinical training and final year students had a score of 99.48±13.96. Dichotomization of data showed statistically significant difference between the mean empathy scores of students studying in the preclinical and clinical years. The difference in the mean empathy scores of male and female students was found to be statistically significant. The JSE-HPS was found to be reliable with Cronbach’s alpha=0.77. Conclusion: The present study revealed a statistically significant decline in empathy levels of undergraduate dental students when the empathy levels of the students studying in the preclinical years and clinical years were compared. The JSE-HPS was found to be a reliable instrument for assessing the empathy levels of dental students. Keywords: Empathy; Communication; Dental education